All Days 2012
DOI: 10.2118/159526-ms
|View full text |Cite
|
Sign up to set email alerts
|

SmartWater Flooding: Industry's First Field Test in Carbonate Reservoirs

Abstract: In recent years, improved/enhanced oil recovery by tuning the ionic composition of injection water has attracted the attention of the petroleum industry, and currently deemed as new emerging research trend. In view of research results for the last four years, we demonstrated in previous reports (SPE 137634; SPEREE Journal, vol. 14(5), pp. 578-593; SPE 143550, SPE 141082, SPE 154076; SPE 154077) that substantial oil recovery beyond conventional waterflooding from carbonates can be achieved by opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(56 citation statements)
references
References 8 publications
2
54
0
Order By: Relevance
“…The new method can be applied to most EOR corefloods, including surfactant, alkali, polymer, or their combinations, and advanced ion management, where selective ions in the injection water are added or removed, or the injection water is diluted (also called low-salinity injection) to obtain EOR (Zhang et al 2007;Seccombe et al 2008;Yousef et al 2010;Gupta et al 2011;Vo et al 2012).…”
Section: Description Of the New Coreflood Methodsmentioning
confidence: 99%
“…The new method can be applied to most EOR corefloods, including surfactant, alkali, polymer, or their combinations, and advanced ion management, where selective ions in the injection water are added or removed, or the injection water is diluted (also called low-salinity injection) to obtain EOR (Zhang et al 2007;Seccombe et al 2008;Yousef et al 2010;Gupta et al 2011;Vo et al 2012).…”
Section: Description Of the New Coreflood Methodsmentioning
confidence: 99%
“…The reduction in brine viscosity offsets the enhancement from favorable wettability alteration (i.e., a favorable relative permeability shift), and ~0% shift in saturation is observed at F w =90% (Figure 14b). The benefit from low salinity injection EOR could be in the single digits (Yousef et al 2012), and oil recovery loss due to salinity reduction could be significant. Since the new method captures shifts both in fractional flow at practical water-cut and relative permeability curves, it can estimate recovery loss due to salinity reduction.…”
Section: Case Study 3: the Effect Of Viscosity Reductionmentioning
confidence: 99%
“…Many experimental techniques (interfacial tension measurement, contact angle measurement, NMR, -potential measurement, imbibition testing, and coreflooding testing) have suggested mechanisms 2 Journal of Chemistry responsible for wettability modifications, such as calcite dissolution [7,8], anhydrite dissolution [9], and surface charge change [10][11][12]. Although the underlying mechanism is still unclear, Yousef et al [13] confirmed the reduction of residual oil saturation through the single well tracer test in field trials.…”
Section: Introductionmentioning
confidence: 99%